Security issues with health care information technology - Mahmoud, Ahmed Mohamed; Zeki, Akram M. (International Journal of Science and Research, 2015)
Nowadays data become one of most important and expensive things in our life. Whereas life became a huge database, content all information in it. However it is not necessary that data be relate to financial area to be expensive and important. While now and in last period, the healthcare sector has become one of the most vulnerable sectors to hack. Why? It is the question that we should ask to understand well the importance of data that contained in this sector. In addition, How? To know how can we protect this sector from hacking or breach. There are many hospitals and clinic hacked in different countries and by different ways. Whereas Data and Information that stole or hacked, most of it was just personal information not financial information such as credit card. It is because this data become more expensive than financial information. On the other hand, There is a question we must to ask: Why attacking increased just in the last period? Are there any relation between it and the increase of medical devices that are connecting on internet? All of that problems or damages cost healthcare organization each year more and more than we can imagine. Thus, must there solutions with less cost for all of that, maybe they will be not the final solution but at least can decrease the damage that effect healthcare organization each year.